2019
DOI: 10.18632/aging.102157
|View full text |Cite
|
Sign up to set email alerts
|

miR-627-3p inhibits osteosarcoma cell proliferation and metastasis by targeting PTN

Abstract: Dysregulation of microRNA (miRNA) has been observed in several types of tumors, including osteosarcoma. Biochip analysis was used to identify miRNAs differentially expressed in osteosarcoma tissues. The targeting sites of miR-627-3p were analyzed using miRDB software and fluorescein reporter gene. MTT and Transwell assays were used to analyze the effects of miR-627-3p on the growth and migration of osteosarcoma cells. Western blotting and real-time PCR were used to detect the effects of miR-627-3p on related p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 23 publications
1
25
0
Order By: Relevance
“…Over the past decades, multiple genomic factors were revealed to be related to OS, including miRNAs [2], lncRNAs [3], and transcription factors [4]. For instance, miR-627-3p was reported to inhibit OS cell proliferation by reducing PTN [5], and miR-548d-3p was reported to inhibit OS by downregulating KRAS [6]. lncRNA TUG1 could promote OS cell metastasis by mediating HIF-1α [7] and AKT signaling [8].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decades, multiple genomic factors were revealed to be related to OS, including miRNAs [2], lncRNAs [3], and transcription factors [4]. For instance, miR-627-3p was reported to inhibit OS cell proliferation by reducing PTN [5], and miR-548d-3p was reported to inhibit OS by downregulating KRAS [6]. lncRNA TUG1 could promote OS cell metastasis by mediating HIF-1α [7] and AKT signaling [8].…”
Section: Introductionmentioning
confidence: 99%
“…The rs6983267 might indicate gain target of hsa-miR-6820-3p, hsa-miR-627-3p, hsa-miR-5190, hsa-miR-4276, hsa-miR-3164, while loss target of hsa-miR-519e-3p, hsa-miR-371a-3p, hsa-miR-33b-3p, hsa-miR-515-3p. Some of them involved in tumorigenesis in current literatures, the downregulation of hsa-miR-627-3p promote osteosarcoma cell proliferation and metastasis; 24 miR-33b-3p also altered the cisplatin sensitivity of cancer cells by impairing the DNA damage response; 25 miR-371a-3 currently reported biomarker for germ cell tumors (GCT), and clinical value of plasma miR-371a-3p level in chemotherapy naive GCT patients is a biomaker to initiate first line of chemotherapy and predict prognosis, 26 , 27 so the rs6983267 might regulate interaction between miR-371a-3 and lncRNA CCAT2 to alter GCT diagnosis and therapy sensitivity; miR-515-3p was markedly overexpressed in individuals with gastric carcinoma compared with that in normal gastric cells (NCs) and the surgery group ( P < 0.0001), and yielded an increase area under the curve (AUC) value with miR-515-3p in model construction. 28 The rs1456315 may bring gain target of hsa-miR-376a-2-5p and loss target of hsa-miR-3149, and hsa-mir-3149 have reported to play important role in DNA repair and immunity by inhibiting expression of ovarian tumor protease deubiquitinase 5 (OTUD5), as a member of the ovarian tumor protease family, 29 therefore rs1456315 and rs6983267 may influence binding between LncRNA and miRNA to modulate epigenetic process.…”
Section: Discussionmentioning
confidence: 99%
“…Data from Chen et al indicated that overexpression of miR-548d-3p reduced osteosarcoma cells growth and migration in vitro by silencing KRAS [15]. Moreover, miR-627-3p and miR-506-3p have been reported to act as tumour suppressors in osteosarcoma by targeting PTN and RAB3D, respectively [16,17].…”
Section: Introductionmentioning
confidence: 99%